2022
DOI: 10.1021/jacs.2c10129
|View full text |Cite
|
Sign up to set email alerts
|

On the Cooperative Origin of Solvent-Enhanced Symmetry-Breaking Charge Transfer in a Covalently Bound Tetracene Dimer Leading to Singlet Fission

Abstract: Singlet fission in covalently bound acene dimers in solution is driven by the interplay of excitonic and singlet correlated triplet 1 (TT) states with intermediate charge-transfer states, a process which depends sensitively on the solvent environment. We use high-level electronic structure methods to explore this singlet fission process in a linked tetracene dimer, with emphasis on the symmetrybreaking mechanism for the charge-transfer (CT) states induced by low-frequency antisymmetric vibrations and polar/pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…To obtain an overview of the importance of CT character for the excited states of DPA compounds, we focus in this work on the analysis of vertical electronic excitations and the solvent effects on the extent of the CT. The use of the ADC(2) method and solvation effects at the COSMO level should provide a balanced description of LE and CT states, as has been shown in previous work 71 . This analysis should already give an interesting insight into the initial stages of the S 1 relaxation, and the electronic character of the lowest excited singlet states with an emphasis on the energetic ordering and coupling of the LE and CT states of DPA‐1.…”
Section: Resultsmentioning
confidence: 80%
“…To obtain an overview of the importance of CT character for the excited states of DPA compounds, we focus in this work on the analysis of vertical electronic excitations and the solvent effects on the extent of the CT. The use of the ADC(2) method and solvation effects at the COSMO level should provide a balanced description of LE and CT states, as has been shown in previous work 71 . This analysis should already give an interesting insight into the initial stages of the S 1 relaxation, and the electronic character of the lowest excited singlet states with an emphasis on the energetic ordering and coupling of the LE and CT states of DPA‐1.…”
Section: Resultsmentioning
confidence: 80%
“…Recently, Mattos et al further studied the role of the SBCT state in SF through a computational study of dimer 13 . 82 They quantified the SF mechanism proposed by Alvertis et al , 118 in which solvent-induced symmetry breaking leads to a high-energy CT state that interacts with the 1 (TT) state, resulting in SF. An approximate assessment of the nonadiabatic interactions between the different electronic states highlighted that the CT state is essential in facilitating the transition from the bright excitonic state to the 1 (TT) state, leading to SF.…”
Section: Covalently Linked Tetracene Oligomersmentioning
confidence: 99%
“…106 However, a CT-assisted mechanism is also adopted in other iSF materials, as evident by the solvent-polarity-dependent SF rate and yield. 24,42,45,74,77,82,[109][110][111][112][113][114][115][116][117][118] The CT state couples strongly with the S 1 and 1 (TT) state via superexchange to serve as an intermediate state for the formation of 1 (TT) whether directly populated or only virtually involved. With the help of this CT-assisted mechanism, highly efficient iSF can still occur in weakly coupled systems.…”
Section: Sf Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent polarity is well-known to affect excited states, particularly CT states. , Depending on the system, high polarity solvents can strongly affect multi-exciton processes, , while also impacting the triplet excited state energy levels . For example, Lukman and co-workers found that for higher polarities, CT states could act as trap states for TIPS-dipentacene.…”
Section: Excitonic Transfermentioning
confidence: 99%